A modified rock mass classification system for TBM tunnels and tunneling based on the HC method of China. (January 2021) - Gong, Qiuming; Lu, Jianwei; Xu, Hongyi; Chen, Zuyu; Zhou, Xiaoxiong; Han, Bei
Abstract: The rock mass classification methods developed to evaluate rock mass stability and tunnel support design for blast and drill tunnels are not suitable to guide tunneling by tunnel boring machine (TBM), such as selection of TBM types, determination of construction scheme and so on. By comprehensively considering the rock mass boreability and stability, a modified rock mass classification system for TBM tunnels is proposed on the basis of the hydropower rock mass classification (HC) method of China. The input parameters are five rock mass parameters as the same as the HC method. In addition, the tunnel diameter is needed to estimate the TBM advance rate. The structure and parameter determination of the classification system are explained and statistically analyzed in details. This system can be applied to evaluate the feasibility of TBM construction and serve as the basis for selection of TBM types and design parameters in the pre-construction phase. Furthermore, it can also be applied to estimate TBM performance and guide tunnel support for a given ground condition in the design phase, and to optimize TBM operational parameters during the construction phase as well. An example is presented to illustrate the application of the proposed system. The limitations of the proposed system and further studies are also discussed. Highlights: A modified rock mass classification system for TBM tunnels and tunneling is developed. The system has the characteristics of simple input parameters and structure. The system can estimate the rock mass stability, boreability and TBM applicability. The database is established with a wide range of rock types and rock mass parameters.